2021
DOI: 10.1016/j.nicl.2021.102658
|View full text |Cite
|
Sign up to set email alerts
|

Multi-compartment analysis of the complex gradient-echo signal quantifies myelin breakdown in premanifest Huntington's disease

Abstract: Highlights Gradient-echo data were acquired from premanifest HD patients in the callosum at 7 T. Reproducibility of multi-compartment analysis across callosal areas was assessed. Reduced myelin water signal fraction (f m ) in HD patients suggested myelin breakdown. Executive function correlated with callosal f m values in HD patients. The reported ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 104 publications
2
6
0
Order By: Relevance
“…As metabolic dysfunction and alterations in energetics play important mechanistic roles in HD (Beal, 2005 ; Browne, 2008 ), these changes may contribute to early microstructural impairment in this callosal portion. The suggestion for myelin impairment in this callosal segment is consistent with a previous study carried out by our group at 7 Tesla (Casella et al, 2021 ), which demonstrated significantly lower myelin water signal fraction in the posterior callosum of premanifest HD patients. Moreover, this suggestion is in accord with the demyelination hypothesis, which argues that early myelinated fibers are more susceptible to myelin disorder in the disease (Bartzokis et al, 2007 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As metabolic dysfunction and alterations in energetics play important mechanistic roles in HD (Beal, 2005 ; Browne, 2008 ), these changes may contribute to early microstructural impairment in this callosal portion. The suggestion for myelin impairment in this callosal segment is consistent with a previous study carried out by our group at 7 Tesla (Casella et al, 2021 ), which demonstrated significantly lower myelin water signal fraction in the posterior callosum of premanifest HD patients. Moreover, this suggestion is in accord with the demyelination hypothesis, which argues that early myelinated fibers are more susceptible to myelin disorder in the disease (Bartzokis et al, 2007 ).…”
Section: Discussionsupporting
confidence: 92%
“…Huntington disease (HD), a neurodegenerative disorder leading to devastating cognitive, psychiatric, and motor symptoms, cannot currently be cured, and a research priority is to increase understanding of its pathogenesis. Subtle and progressive white matter (WM) alterations have been observed early in HD progression (Casella et al, 2021 ; Gregory et al, 2019 ; McColgan et al, 2015 ; McColgan et al, 2017 ; McColgan et al, 2018 ; Paulsen et al, 2008 ; Scahill et al, 2020 ), but their etiology and role remain unclear. Therefore, the present study aimed to disentangle the contribution of changes in axon microstructure versus changes in magnetization transfer as a proxy measure of myelin and/or iron, to WM pathology in premanifest HD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The posterior section of the corpus callosum showed lower MWF values than controls. Significant correlations were found between MWF in the posterior corpus callosum and the individuals’ scores on executive function but the MWF was not related to proximity to disease onset [36 ▪▪ ].…”
Section: Huntington's Diseasementioning
confidence: 83%
“…Recent investigations in HD have recognized alterations in the brain's white matter (WM) as relevant pathophysiological feature of HD [1][2][3][4][5][6][7][8][9][10][11][12] . Specifically, WM atrophy has been shown both in animal models and in human HD carriers by histopathological post-mortem studies [13][14][15][16][17] , and MRI studies 2,4,5,11,[17][18][19][20][21] . For example, structural neuroimaging studies of HD carriers have shown that WM atrophy can be found across several WM areas, including the corpus callosum (CC), the anterior commissure, internal and external capsules, and the cingulum.…”
Section: Introductionmentioning
confidence: 99%